Territorial embeddedness of sustainable agri-food systems. A systematic review - Duarte, Luís (2025)
The current food systems require an urgent transition toward more sustainable food landscapes. One key discussion arising is on the potential of territorial approaches to foster the sustainability of agri-food systems, for which this paper provides a review. This systematic literature review is based on bibliometric methods which allowed us to identify in a fairly unbiased manner the most impactful authors, papers, and research trends. Three distinctive scientific fronts are identified, revealing research specializations defined by their distinctive social-territorial approach: sustainable agroecosystems at the farm level; agroecological initiatives at the community level; and transformation of the food system and societal values at the regional/national level. We expect this review will trigger and enrich further discussions about future trends and opportunities for enhancing the sustainability of agri-food systems. This is especially urgent since research on these topics is relatively recent, and conflicting approaches are identified for which an overall understanding of potential solutions is largely missing. Reconciling agricultural and biodiversity sustainability stands on top of current political agendas, and thus providing an overall picture of how territorial approaches confront this problem shall prove key in guiding better-informed land policy and management decisions.